Calcifilaxia, desafio diagnóstico e terapêutico: Relato de um caso bem sucedido - Roncada, Eduardo Vinicius Mendes; de Abreu, Marilda Aparecida Milanez Morgado; Pereira, Mayra Falcão; de Oliveira, Claúdia Cardoso Macedo; Nai, Gisele Alborghetti [UNESP]; Soares, Deusita Fernandes Gandia (FapUNIFESP (SciELO), 2012)
Calciphylaxis, also known as calcific uremic arteriolopathy, is a severe complication often observed in patients with hyperparathyroidism secondary to chronic renal failure, which occurs mainly in women. It is characterized by ischemic tissue loss secondary to progressive vascular compromise. This is a rare and severe condition and its pathogenesis is unclear. The best treatment is prevention, especially in order to maintain adequate levels of calcium and phosphorus. We describe a case of this disease in a patient with hyperparathyroidism secondary to chronic renal failure who underwent medical treatment, surgical debridement and total skin autografts, with resolution of symptoms after 6 months. © 2012 by Anais Brasileiros de Dermatologia.
Calciphylaxis, a diagnostic and therapeutic challenge: Report of a successful case
Keywords: Blood vessels; Calcium metabolism disorders; Chronic; Hyperparathyroidism; Ischemia; Renal insufficiency; Secondary